Foreign Protein Detection in Transgenic Rice Revealed by Comparative Proteomic Analysis. Issue 5 (1st September 2015) - Yang, Yanhua; Dai, Li; Zhu, Keming; Xia, Hengchuan; Chen, Liang; Liu, Hailong; Chen, Keping
ABSTRACT: To investigate whether the foreign protein in transgenic rice ( Oryza sativa L.) can be detected and then characterize the different proteins between transgenic rice and nontransgenic rice, we employed proteomic tools including two‐dimensional electrophoresis (2‐DE) and mass spectrometry (MS) to globally identify different proteins between Bt ‐'Minghui 63' (MH63) (with the fused Cry1Ab–Cry1Ac gene) and its nontransgenic control MH63. In all, 37 statistically different proteins between Bt ‐MH63 and MH63 were successfully identified, including six unique proteins in Bt ‐MH63. Gene ontology analysis showed that these six unique proteins were mainly involved in metabolic, catalytic, binding, and antioxidant process. Among these six unique proteins, two non‐rice source proteins, phosphinothricin‐ N ‐acetyltransferase, were only expressed in germinating seed and seedling of Bt ‐MH63, but not in MH63, which were further confirmed by matrix‐assisted laser desorption–ionization time of flight (MALDI‐TOF) MS–MS analysis. Our work suggests that a comparative proteomic approach may be feasible for identifying foreign proteins and genes in rice.